Chalcone Isomerase a Key Enzyme for Anthocyanin Biosynthesis in Ophiorrhiza japonica - Sun, Wei; Shen, Huan; Xu, Hui; Tang, Xiaoxin; Tang, Ming; Ju, Zhigang; Yi, Yin (Frontiers in Plant Science, 2019)
Anthocyanins are distributed ubiquitously to the terrestrial plants and chalcone isomerase (CHI) catalyzed the stereospecific isomerization of chalcones is a committed step in the anthocyanin biosynthesis pathway. In this study, one gene encoding CHI was isolated from Ophiorrhiza japonica and designated as OjCHI. Multiple sequence alignments and phylogenetic analysis revealed that OjCHI had the conserved CHI active site residues and was classified into type I CHI group. In order to better understand the mechanisms of anthocyanin synthesis in Ophiorrhiza japonica, integrative analysis between metabolites and OjCHI expression was conducted. The results showed OjCHI expression matched the accumulation patterns of anthocyanins not only in different tissues but also during the flower developmental stages, suggesting the ptotential roles of OjCHI in the biosynthesis of anthocyanin. Then biochemical analysis indicated that recombinant OjCHI protein exhibited a typical type I CHI activity which catalyzed the production of naringenin from naringenin chalcone. Moreover, expressing OjCHI in Arabidopsis tt5 mutant restored the anthocyanins and flavonols phenotype of hypocotyl, cotyledon and seed coat, indicating its function as a chalcone isomerase in vivo. In summary, our findings reveal the in vitro as well as in vivo functions of OjCHI and provide a resource to understand the mechanism of anthocyanin biosynthesis in Ophiorrhiza japonica.